2021
DOI: 10.3390/plants11010086
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Phytoextraction Potential by Genome Editing and Transformation: A Review

Abstract: Soil metal contamination associated with productive activities is a global issue. Metals are not biodegradable and tend to accumulate in soils, posing potential risks to surrounding ecosystems and human health. Plant-based techniques (phytotechnologies) for the in situ remediation of metal-polluted soils have been developed, but these have some limitations. Phytotechnologies are a group of technologies that take advantage of the ability of certain plants to remediate soil, water, and air resources to rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 129 publications
(153 reference statements)
0
6
0
Order By: Relevance
“…The widely used gene editing approaches such zinc finger nucleases (ZFNs) and transcript activators like effector nucleases (TALENs) is limited due to the frequent mutations at non-targeted sites (Sarma et al, 2021). The CRISPR-Cas9 (clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9) system has emerged as an innovative gene editing tool in plant systems (Venegas-Rioseco et al, 2021). It is a quick, cost friendly tool that can be used for improving crop traits against abiotic and biotic stress tolerance (Pandita, 2021).…”
Section: Genetic Engineering Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…The widely used gene editing approaches such zinc finger nucleases (ZFNs) and transcript activators like effector nucleases (TALENs) is limited due to the frequent mutations at non-targeted sites (Sarma et al, 2021). The CRISPR-Cas9 (clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9) system has emerged as an innovative gene editing tool in plant systems (Venegas-Rioseco et al, 2021). It is a quick, cost friendly tool that can be used for improving crop traits against abiotic and biotic stress tolerance (Pandita, 2021).…”
Section: Genetic Engineering Approachesmentioning
confidence: 99%
“…The CRISPR–Cas9 (clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9) system has emerged as an innovative gene editing tool in plant systems ( Venegas-Rioseco et al., 2021 ). It is a quick, cost friendly tool that can be used for improving crop traits against abiotic and biotic stress tolerance ( Pandita, 2021 ).…”
Section: Various Approaches To Ameliorate Heavy Metal Stress In Medic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic methods are not only used to convert functional genes but also to elevate particularly recognized promoters to existing gene functions connected with metal accumulation/translocation/detoxification mechanisms and introduce them to target bacteria ( Pratush et al, 2018 ). As a low molecular weight, cysteine-rich protein, metallothioneins (MTs) found in many bacteria have the ability to bind metals and form complex biochemical structures ( Venegas-Rioseco et al, 2022 ). Some gene transformation experiments have convincingly demonstrated that MT S produced by PGPB (e.g., P. putida and Mycobacterium tuberculosis ) can improve plant tolerance to metals ( Mierek-Adamska et al, 2017 ; Nanda et al, 2019 ).…”
Section: Genetically Modified Organisms For Bioremediationmentioning
confidence: 99%
“…These modifications facilitate to control and stabilize the harmful effects of environmental pollutants on various crop plants. CRISPR-Cas9-based gene editing offers exciting options for photo technologies such as phytoremediation [ 193 ]. Several phytoremediators have been sequenced such as Thlaspi caerulescens (hyper-accumulator for Ni, Zn, and Cd), Arabidopsis halleri (hyper-accumulator for Zn and Cd), Hirschfeldia incana (for controlling Pb), Brassica juncea , and Pteris vittata [ 194 , 195 , 196 , 197 ].…”
Section: Crispr For Improving Plant Tolerance To Climate Changementioning
confidence: 99%